Analysis of The Effect of Elephant Grass (Pennisetum purpureum) Cutting Length on Silage Characteristics with a Shelf Life of 63 Days - Azizah, Alfira Nurul; Sosiawati, Endang Sapta Hari; Dianingtyas, Brilian Desca (Open Global Scientific Journal, 2024)
Background: One of the feed preservation techniques is silage to anticipate forage shortages in the dry season. One of the factors that affect the characteristics of silage is the length of grass cutting.Aims: The purpose of this study was to determine the effect of the length of elephant grass cutting (Pennisetum purpureum) on the quality of silage characteristics including physical, chemical and biological qualities with a shelf life of 63 days.Methods: The method used was an experiment with a Completely Randomized Design (CRD) design, the treatment used was the length of elephant grass cutting, with cutting levels of 3 cm, 5 cm, and 7 cm, each treatment was repeated 5 times and stored for 63 days. The variables observed were the physical characteristics of silage including texture, color, aroma using organoleptic tests with 15 somewhat trained panelists, then the chemical characteristics test by measuring the pH value of the silage and the biological characteristics test by assessing the presence of fungi in the silage. Data analysis used was the ANOVA test (analysis of variance) using the F test. If the F test shows a significant or very significant effect, it is continued with Duncan’s Multiple Range Test (DMRT) test.Results: The results of statistical analysis of the effect of elephant grass cutting length on silage characteristics showed that P1, P2, and P3 had no significant effect on texture, aroma, and pH value (P>0.05), while on color and the presence of fungi there was a significant effect (P<0.05). The conclusion of this study is that there is no significant effect on texture, aroma, and pH value of silage, while on color and the presence of fungi silage there is a significant effect. Suggestions for further research are expected to conduct further analysis on color, fungi, proximate tests, and palatability tests.